Evaluation of Th2 and Th17 Immunity-Related Factors as Indicators of Brucellosis - Gheitasi, Reza; Keramat, Fariba; Khosravi, Sara; Hajilooi, Mehrdad; Pletz, Mathias W.; Makarewicz, Oliwia (Frontiers in Cellular and Infection Microbiology, 2022)
Objective Brucellosis is a common bacterial zoonotic infection, and greater than half a million new cases are diagnosed annually. This study investigates the expression of Th2 and Th17 immunity-related factors (Th2-LCR lncRNA, IL-25, TRAF3IP2, and IL-17RB) in different stages of Brucella infections. Material and Methods In total, 99 brucellosis patients were divided into three groups (acute = first infection before treatment, relapse = before treatment, and treated = after treatment for 6–8 weeks with doxycycline and rifampin). Thirty-three healthy volunteers represented the control group. Gene expression levels were assessed by quantitative amplification in reference to the 18S rRNA gene and statistically evaluated. Results No significant differences in the expression of these genes were observed between the control group and patients after completion of antibiotic treatment. Compared to these two groups, only Th2-LCR lncRNA and TRAF3IP2 were significantly more highly expressed in the acute group. Th2-LCR lncRNA was also significantly elevated in the relapse group. TRAF3IP2 expression was additionally significantly increased in the acute group compared to the relapse group. Conclusion IL-25 and IL-17RB failed to differentiate between the infected and noninfected groups. TRAF3IP2 and Th2-LCR lncRNA might be good indicators of brucellosis during the acute phase, but the expression levels varied strongly among patients. To verify the suitability of these factors as an indicator for brucellosis, acute infection or relapse should be investigated in further studies on larger cohorts with well-defined inclusion criteria.